The Criminal Procedure Code (KUHAP) as an Instrument for Assessing Judges’ Compliance with the 10 Points of the Code of Ethics and Guidelines for Judges’ Conduct (KEPPH) in Criminal Trials - Junaidi Syamfran (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study analyzes the position of Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP 2025) as an instrument for assessing judges’ compliance with the 10 Points of the Code of Ethics and Guidelines for Judges’ Conduct (KEPPH) in criminal trials. The KUHAP update is not only intended as a technical adjustment to the enactment of the new KUHP, but also as a means of integrating judicial ethical values into binding criminal procedure law norms. This study uses normative legal methods, drawing on statutory, conceptual, and Critical Legal Studies (CLS) approaches. The results show that the 2025 KUHAP has systematically internalized the KEPPH principles into various procedural provisions, ranging from justice, honesty, and wisdom to independence, integrity, responsibility, judicial dignity, discipline, humility, and the professionalism of judges. However, from a CLS perspective, this integration has not fully dismantled the structural power relations in the criminal justice system. Juridified ethical norms still have the potential to be reduced to formal compliance if they are not accompanied by judges’ critical awareness of the structural inequalities inherent in judicial practice. Therefore, the effectiveness of the 2025 Criminal Procedure Code as an instrument for evaluating judicial ethics depends heavily on the transformation of judicial awareness toward substantive justice.